Sensitivity of Shear and Longitudinal Velocity to Compression and Shear Stress Paths in Cohesive Soils - McAneny, George. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Civil Engineering.; Advisor: John Germaine.; Committee: Lucy Jen, Luis Dorfmann, and Richard Plumb.; Keyword: Geotechnology.